The 'SMSA' Scoring System for Determining the Complexity of a Polyp. (13th March 2011) - Gupta, S; Miskovic, D; Bhandari, P; Dolwani, S; McKaig, B; Pullan, R; Rembacken, B; Rutter, M D; Riley, S; Valori, R; Vance, M E; Faiz, O D; et al.
Abstract : Introduction: It may be possible to identify several 'levels' of polypectomy service within the UK, each requiring a different range of polypectomy skills: flexible sigmoidoscopy screening, non-screening colonoscopy, screening colonoscopy and the specialist endoscopy service. This requires a definition of 'complexity levels' of polyps, to reflect the four levels of service, each with clearly defined parameters that represent the bare minimum that an endoscopist operating at a particular level should be able to deal with competently. Methods: The aim of this study was to define polyp levels to reflect the four levels of competency required to deliver a particular service, based on polyp characteristics. Consensus by nine experienced endoscopists regarding the parameters that determine the complexity of a polyp, was achieved using group meetings and the Delphi method. The same group of experts then assigned a polyp complexity level to each possible combination of factors. Results: The group identified four factors to be most relevant for determining the complexity of a polypectomy: size (S), morphology (M), site (S) and access (A). In two Delphi rounds the benchmarks for each factor were evaluated (see table). After analysing the expected complexity for each polyp type as proposed by the experts, a scoring system was established, based on size (1–9 points), morphology (1–3 points), site (1–2 points) and access (1–3 points). Four polyp levels (with increasing level of complexity) were identified based on the range of expert scores obtained: Level 1 (4–5), Level 2 (6–9), Level 3 (10–12) and Level 4 (>12). Conclusion: Defining polyp complexity levels may be useful for planning training, competency assessment and certification in colonoscopic polypectomy. In turn this may allow for more efficient service delivery and referral onto specialist centres where appropriate. Competing interests: None.